Prospects and Constraints of Onion Production and Marketing: A Case Study of District Tando Allahyar, Sindh-Pakistan: Prospects, Profitability and Constraints of Onion Production & Marketing - Khan, Muhammad Nisar; Malik, Arshad Mahmood; Gulnaz Hameed; Saima Asad (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
This study aimed to identify the existing onion production practices and constraints at smallholder farms and profitability of onion in the Tando Allahyar district of Sindh during the year 2018-19. The primary data were collected from 24 randomly chosen onion-producing farmers in village Ibrahim Shah using a pre-tested systematic questionnaire. Descriptive statistics were used to evaluate percentages, frequency, and mean, while the benefit-cost analysis (BCA) method was used to determine onion growers' profitability. Results of the study revealed that the overall average total cost and gross revenue of onion production were (Rs. 115120/acre, Rs. 154875/acre) respectively. The benefit-cost ratio was found to be 1.52 for (variable costs) and 1.35 for (total cost), indicating that onion cultivation benefits farmers in the Tando Allahyar district. The most common and local onion variety grown was Nasarpuri, which was cultivated by 87 % of farmers, along with Hazari and Phulkara. However, the farmers were reluctant to use hybrid seeds due to their inability to withstand high temperatures. The main production constraints for onion growers were high input prices, particularly seed costs, and high labour charges for hoeing and weeding. Similarly, low product prices and high transportation costs were major marketing constraints. Due to a lack of technical expertise with current technology, such as a shortage of cold storage and skilled labor, the marketing of excess produce throughout the year was a significant problem for onion growers. It is therefore suggested that a comprehensive marketing capacity building and Global GAP will improve the quality, productivity and profitability of the farmers and open the channel of export for Pakistan.